Personal Names of Vilnius Residents in the 16th–17th Centuries - Alma Ragauskaitė (Onomástica desde América Latina)
Documents of municipal self-government institutions are among the most important historical anthroponymy sources of the Lithuanian burgher estate. Town register books of Kaunas since the beginning of the 16th century are unique due to their chronological aspect. The research described in this article focuses on the recordings of 102 Vilnius residents (temporary visitors) made in 1551–1683. It aims to analyse the binary naming of individuals, the specificity of surname structure and to discern the stratum of personal names having Lithuanian origin. Also, efforts are made to identify factors determining the recording of anthroponymic forms in administrative manuscripts. However, records of historical sources would not be informative, devoid of the historical and social contexts. Hence, the discussion extends into relevant history fragments of Kaunas and Vilnius cities in the 16th–17th centuries. Several research methods, i.e., descriptive, comparative and reconstructive, were purposely applied to study the collected historical anthroponymic material extensively. Traditional Christian names were predominant among the examined recordings. The surnames of Vilnius residents are of patronymic and non-patronymic origin. The most popular were Slavic patronymic suffixes -(i)evič and -(i)ovič. In town register books of Kaunas, anthroponyms of Vilnius residents (Lithuanian nationals) were Slavicised in various ways. This situation was influenced by the specificity of legal documents, the competence of scribes and the Polonisation of Lithuanian anthroponyms. No consistency or uniformity was observed while recording Vilnius residents in town register books of Kaunas of the 16th–17th centuries. Long minutes of magistrate meetings and court sessions were handwritten. Surnames were only the textual elements in such extensive manuscripts. This article continues a short list of efforts on the historical anthroponymy of Lithuanian townspeople (Zinkevičius 1976, 1977, Ragauskaitė, 2003, 2005). The provided historical anthroponymic material, its analysis, and its conclusions will be relevant to the research of historical anthroponomy, town history, and the ethnic composition of townspeople (Kiaupa, 2010).